One Step In Situ Loading of CuS Nanoflowers on Anatase TiO2/Polyvinylidene Fluoride Fibers and Their Enhanced Photocatalytic and Self-Cleaning Performance - Zhang, Z.-G. (Springer New York LLC, 2021)
10.1186/s11671-019-3052-5